CO2 capture via catalytic hydrogenation to methanol: Thermodynamic limit vs. 'kinetic limit - Fornero, Esteban Luis (2011)
The production of methanol via the catalytic hydrogenation of carbon oxides was simulated in a reacting system that included the recycling of noncondensable gases (H2, CO2 and CO) to evaluate the CO2 capture capability of the process. As a first step, the asymptotic responses of the system 'operating in thermodynamic equilibrium' (i.e., overall recoveries of CO2 and H2, CH3OH selectivity and productivity) were analyzed for various industrial conditions of pressure (3-5 MPa), temperature (508-538 K), feed composition (H 2/CO2 = 1.5/1 to 4/1) and mole recycle ratio (R) with respect to the molar feed flow rate. Then the performance of two catalysts (a novel one, Pd-Ga2O3/SiO2 and a commercial CuO/ZnO/Al2O3 type) in an ideal isothermal, isobaric, pseudohomogeneous fixed-bed reactor was studied for a broad range of W/FCO 2 ratios. It was found that, whereas the 'reactor in equilibrium' would allow up to 100% CO2 capture, the capture values upon using these catalysts were significantly lower. Nevertheless, such recoveries always increased whenever R was raised, which implies that catalyst development efforts in this field should prioritize achievement of the highest catalytic activity (i.e., specific productivity) rather than attempt catalyst selectivity improvements.